FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA PEGAWAI KANTOR CAMAT BUBON KABUPATEN ACEH BARAT - Meri Jasmiana; Nabila Hilmy Zhafira (Fakultas Ekonomi Universitas Warmadewa, 2022)
The results of the research conducted by researchers are to analyze the performance of employees at the Bubon sub-district office, West Aceh Regency, which influences the workplace and work motivation. In this study, researchers obtained data through data collection techniques using sampling techniques and data collection used by researchers was a questionnaire that was submitted to respondents using the likert scale through quantitative research methods. The population that the researchers took at the time of conducting this research were all employees of the Bubon sub-district office, thus the number of samples taken as respondents was 30 people. By using simple regression testing testing using the IBM Statistics 24 application that has been carried out by researchers, the researchers show that the influence of the work environment is closely related to the performance of employees in Bubon sub-district. Then the existence of work motivation can increase the enthusiasm and positive competitiveness of the work of the employees.